Pseudo-resonance structures in chiral alcohols and amines and their possible aggregation states - Zhu, Huajie; Li, Shengnan; Jia, Yunjing; Jiang, Juxing; Hu, Feiliu; Li, Longfei; Cao, Fei; Wang, Xiaoke; Li, Shenhui; Ouyang, Guanghui; Tian, Gengfang; Gong, Ke; et al. (Frontiers in Chemistry, 2022)
We now report that some chiral compounds, like alcohols, which are not sterically hindered atropisomers nor epimer mixtures, exhibit two sets of simultaneous NMR spectra in CDCl3. Some other chiral alcohols also simultaneously exhibit two different NMR spectra in the solid state because two different conformers, A and B had different sizes because their corresponding bond lengths and angles are different. These structures were confirmed in the same solid state by X-ray. We designate these as pseudo-resonance for a compound exhibiting several different corresponding lengths that simultaneously coexist in the solid state or liquid state. Variable-temperature NMR, 2D NMR methods, X-ray, neutron diffraction, IR, photo-luminesce (PL) and other methods were explored to study whether new aggregation states caused these heretofore unknown pseudo-resonance structures. Finally, eleven chiral alcohols or diols were found to co-exist in pseudo-resonance structures by X-ray crystallography in a search of the CDS database.